THE INFLUENCE OF PARENTS ATTENTION AND LEARNING MOTIVATION TO THE RESULT OF STUDENTS LEARNING IN THE LESSON OF ECONOMY IN THE ELEVEN CLASS IN THE JUNIOR HIGH SCHOOL 1 PADANG GANTING - Yanti, Ayu Nofri (Pendidikan Ekonomi, 2014)
The research is have the goal to know : (1) The influence of parents attention to the resultof students learning in the lesson of economy in the eleven class in the junior high school 1Padang Ganting. (2) The influence of motivation learning to the result of students learning in thelesson of economy in the eleven class in junior high school 1 Padang Ganting. (3) The influence ofparents attention and learning motivationway together to the result of students learning in theeleven class lesson of economy junior high school 1 Padang Ganting at the 2014/2015 with sampletotal is 77 students. The technics of take sample is sampleing total. The instrument used to theresearch is poll which used data analyse the experiment proper model , the classicasumsiationexperiment, regression linear multiplied analyse, determination cofisienand hypothesis experiment.The result of research to point out that : (1) To be found the positive influence significationbetween the parents attention to the result of students learningin the lesson of economy in theeleven class in junior high school 1 padang ganting. (2) To be found the positive influence andsignification between learning motivation to the result of students learningin the lessonof economyin the eleven class in junior high school 1 padang ganting. (3) To be found the positive influenceand signification between parents attention and learning motivation is way together to the result ofstudents learningin the lesson ofeconomy in the eleven class in junior high school 1 padang gantin